Analisis Objek Kajian Fonetik dan Implikasinya terhadap Pembelajaran Literasi di Sekolah Dasar - Pohan, Jeni; Fahira, Mauliza; Nadila, Izmi; Jabila, Fatia Zam (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
This study aims to analyze the object of phonetics study and its implications for literacy learning in elementary school students. The study is based on the importance of understanding speech sounds (phonetics) as a foundation for effective early reading skills. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group model, complemented by qualitative methods through observation and interviews. The subjects were first-grade students from two elementary schools with similar characteristics. The results revealed that the phonics method significantly improved students’ early reading abilities compared to traditional approaches. Qualitative data also indicated that phonics instruction supported students in associating sounds with letters and increased their learning motivation.